2021
DOI: 10.1093/pubmed/fdab113
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and mental health during the COVID-19 pandemic in Japan

Abstract: Background The coronavirus disease (COVID-19) pandemic is an unprecedented public health crisis, but its effect on suicide deaths is little understood. Methods We analyzed data from monthly suicide statistics between January 2017 and October 2020 and from online surveys on mental health filled out by the general population in Japan. Results Compared to the 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
102
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 17 publications
8
102
1
2
Order By: Relevance
“…In contrast, the number of low-risk 2020 students was high, whereas that of high-risk 2021 students was high in suicidal ideation. This is consistent with the findings of Ueda et al [ 21 ], which suggested that the number of suicide deaths during the initial phase of the pandemic was lower than average but exceeded the past trend from July 2020. The data for the 2020 first-year students in this study were from May 2020.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the number of low-risk 2020 students was high, whereas that of high-risk 2021 students was high in suicidal ideation. This is consistent with the findings of Ueda et al [ 21 ], which suggested that the number of suicide deaths during the initial phase of the pandemic was lower than average but exceeded the past trend from July 2020. The data for the 2020 first-year students in this study were from May 2020.…”
Section: Discussionsupporting
confidence: 93%
“…The finding that lonely individuals in Japan may be at increased risk for worse mental health is a cause for concern. Depression and anxiety have not only been linked to worse COVID-19-related outcomes (decreased use of preventive behaviours) in this setting ( Stickley et al, 2020 ) but poorer mental health may also exacerbate the effects of loneliness on other detrimental outcomes such as suicidal behaviour ( Stickley and Koyanagi, 2016 ), while there is evidence that suicide mortality may have risen in some population subgroups in Japan during the pandemic ( Ueda et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Since our study reported depression in 44.8% and generalized anxiety disorder in 21.4%, the prevalence of depression and generalized anxiety disorder in PLWH was approximately the same in other countries. In the general population of Japan, depression and generalized anxiety disorder were reported to be 18.3% and 10.6%, respectively, during the COVID-19 pandemic [7]. PLWH living in Japan may be far more stressed and more than twice as depressed and anxious as people without HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported that COVID-19 caused anxiety, stress, and depression in about 30% of the general population in Asia and Europe [6]. In Japan, the prevalence of people with depression increased to 18.3%, with at least one of the most common anxiety disorders increasing to 10.6% during the pandemic [7]. It has been suggested that substantial lockdowns may cause psychological distress, depression, and anxiety [8][9][10][11], although stringent responses such as social distance and restrictions on going out are necessary to prevent the spread of COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%